Developing Balanced Nutrition Snakes and Ladders as Educational Media for Balanced Nutrition Tumpeng on Elementary School Student - Kurnia, Arif Rahmat; Susilo, Mursid Tri; Mardiana, Mardiana (Study Program of Nutrition, Public Health Faculty, Institut Kesehatan Helvetia, 2018)
Balanced nutrition tumpeng is a health promotion media created by the health ministry to replace the four healthy five perfect. This tumpeng was made in 2014, but the socialization is still not evenly distributed. No children in Kalikayen Village were detected as having malnutrition in the last 5 years but instead tended to be overweight so they were at risk of degenerative diseases. Objective; to determine the ability of snakes and ladders to be balanced nutrition in increasing students' knowledge. Materials and Methods; type of research is experimental with the design of one group pre-post test design. This study involved 36 grade IV and V students from Kalikayen 2 Public Elementary School with the intervention in the form of a game of snake tumpeng ladder balanced nutrition. Results; the results of the Wilcoxon test between pre-test and post-test obtained p = 0.011 with a significance level of 0.05 so that there was a significant difference before and after the intervention. Conclusion; the use of balanced nutrition tumpeng snakes and ladder has been proven to be able to increase knowledge about balanced nutrition.